2006
DOI: 10.1002/dvdy.21022
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of scale β‐keratins in the differentiating epidermis of geckoes show they are glycine‐proline‐serine–rich proteins with a central motif homologous to avian β‐keratins

Abstract: The ␤-keratins constitute the hard epidermis and adhesive setae of gecko lizards. Nucleotide and amino acid sequences of ␤-keratins in epidermis of gecko lizards were cloned from mRNAs. Specific oligonucleotides were used to amplify by 3-and 5-rapid amplification of cDNA ends analyses five specific gecko ␤-keratin cDNA sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 31 publications
6
67
0
Order By: Relevance
“…The present immunoblotting and immunolocalization survey confirms that the deduced epitopes through molecular biology methods (Dalla Valle et al,2005,2007a,b,2008,2009,2010; Hallahan et al,2008; Alibardi et al,2009; Ye et al,2010) are present in alpha‐keratins and beta‐proteins of the epidermis in chelonians, crocodilians, and lepidosaurians. The specificity for the epitope recognition through the employed antibodies is demonstrated by the disappearing of immunolabeled bands after preabsorbing with the peptide (Figs.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The present immunoblotting and immunolocalization survey confirms that the deduced epitopes through molecular biology methods (Dalla Valle et al,2005,2007a,b,2008,2009,2010; Hallahan et al,2008; Alibardi et al,2009; Ye et al,2010) are present in alpha‐keratins and beta‐proteins of the epidermis in chelonians, crocodilians, and lepidosaurians. The specificity for the epitope recognition through the employed antibodies is demonstrated by the disappearing of immunolabeled bands after preabsorbing with the peptide (Figs.…”
Section: Discussionsupporting
confidence: 80%
“…Their genes are activated only in suprabasal or precorneous keratinocytes as it is typical for specialized corneous proteins. The gene structure of these proteins (Dalla Valle et al,2005,2007a,b;2008,2010) is similar to that of avian genes for feather or phi‐keratins (Brush,1983, Gregg and Rogers,1986). Furthermore, their initial basic pI suggests that they are complementary proteins to the acidic‐neutral alpha‐keratins present in reptiles where basic alpha‐keratins are almost absent (Alibardi and Toni,2006, Toni et al, 2007).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent molecular biology and proteomic studies have sequenced some genes and proteins as β-keratins (Dalla Valle et al ., 2005, 2007). These molecules comprise glycine-proline-rich and cystein-proline-rich proteins of 13–19 kDa.…”
Section: Evo-devomentioning
confidence: 99%
“…More recent studies on the proteins and genes of reptilian beta‐keratins (Dalla Valle et al, , ,b, ,b; Hallahan et al, ) have indicated that these small proteins are not keratins since they are not intermediate filament proteins. These small proteins correspond to specific KAPs evolved in sauropsids that are, case so far unique among vertebrates, capable to form themselves filamentous structures (Fraser et al, ; Brush, ; Fraser and Parry, ) that mix with those of intermediate filaments (Alibardi and Toni, , ; Alibardi et al, , ; Toni et al, ).…”
mentioning
confidence: 99%